DNA Sensor IFI204 Contributes to Host Defense Against Staphylococcus aureus Infection in Mice - Chen, Wei; Yu, Shui-Xing; Zhou, Feng-Hua; Zhang, Xiao-Jing; Gao, Wen-Ying; Li, Kun-Yu; Liu, Zhen-Zhen; Han, Wen-Yu; Yang, Yong-Jun (Frontiers in Immunology, 2019)
Interferon-inducible protein IFI204 (p204, the murine homolog of human IFI16) is known as a cytosolic DNA sensor to recognize DNA viruses and intracellular bacteria. However, little is known about its role during extracellular bacterial infection. Here we show that IFI204 is required for host defense against the infection of Staphylococcus aureus, an extracellular bacterial pathogen. IFI204 deficiency results in decreased survival, increased bacterial loads, severe organs damage, and decreased recruitment of neutrophils and macrophages. Production of several inflammatory cytokines/chemokines including IFN-β and KC is markedly decreased, as well as the related STING-IRF3 and NF-κB pathways are impaired. However, exogenous administration of recombinant KC or IFN-β is unable to rescue the susceptibility of IFI204-deficient mice, suggesting that other mechanisms rather than KC and IFN-β account for IFI204-mediated host defense. IFI204 deficiency leads to a defect in extracellular bacterial killing in macrophages and neutrophils, although bacterial engulf and intracellular killing activity are normal. Moreover, the defect of bactericidal activity is mediated by decreased extracellular trap formation in the absence of IFI204. Adoptively transferred WT bone marrow cells significantly protect WT and IFI204-deficient recipients against Staphylococcus infection compared with transferred IFI204-deficient bone marrow cells. Hence, this study suggests that IFI204 is essential for the host defense against Staphylococcus infection.